2015
DOI: 10.5539/jas.v7n5p28
|View full text |Cite
|
Sign up to set email alerts
|

Rearing Larvae of Different Strains of Coregonus lavaretus under Cold Water Conditions: Comparison of a Special Cold-Water Line with a Standard Agglomerated Microdiet

Abstract: We studied the performance of a commercial, agglomerated larval microdiet in terms of survival, growth and feed acceptance and compared a dedicated "cold water line" of the product to the standard product involving a Baltic and an Alpine strain of whitefish. Experiments were conducted under cold water conditions < 8 °C (average 5.1 °C) for 60 days after hatching. Replicate tanks of 400 and 200 liter volume received filtered lake water disinfected with ozone and UV light and were stocked with 15 larvae per lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
5
3
Order By: Relevance
“…In several studies mean larval survival was as low as 5% (Lahnsteiner & Kletzl, ), 11.1% (Esmaeilzadeh‐Leithner & Wanzenböck, ) or 20% (Hundt et al, ). The survival rate for the worst performing groups (treatment A) in this trial (40.2%–49.3%) was slightly higher than that in the range of experiments with Coregonus lavaretus (Champigneulle & Rojas‐Beltran, ; Leithner & Wanzenböck, ). The groups from treatments B and C revealed survival rates of 57.3%–74.5% and were comparable to a shorter trial by Hundt et al () until 16 dph with 60% and the better performing groups in the experiments of Esmaeilzadeh‐Leithner and Wanzenböck () as well as in the 28‐day study of Sebesta et al ().…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In several studies mean larval survival was as low as 5% (Lahnsteiner & Kletzl, ), 11.1% (Esmaeilzadeh‐Leithner & Wanzenböck, ) or 20% (Hundt et al, ). The survival rate for the worst performing groups (treatment A) in this trial (40.2%–49.3%) was slightly higher than that in the range of experiments with Coregonus lavaretus (Champigneulle & Rojas‐Beltran, ; Leithner & Wanzenböck, ). The groups from treatments B and C revealed survival rates of 57.3%–74.5% and were comparable to a shorter trial by Hundt et al () until 16 dph with 60% and the better performing groups in the experiments of Esmaeilzadeh‐Leithner and Wanzenböck () as well as in the 28‐day study of Sebesta et al ().…”
Section: Discussioncontrasting
confidence: 54%
“…There are a few older studies regarding the first feeding of coregonids stating that a first feeding with a pure dry feed diet is possible (Flüchter, ; Mamcarz et al, ) but similar to the current study, other researchers have also found that using live feed, to at least some extend, results in higher larvae survival and growth (Champigneulle & Rojas‐Beltran, ; Drouin, Kidd, & Hynes, ). More recent studies indicate the improvement of the available dry feeds and understanding of first feeding with good results on a dry feed diet only (Esmaeilzadeh‐Leithner & Wanzenböck, ; Lahnsteiner & Kletzl, ; Leithner & Wanzenböck, ). The usage of live feed for Coregonus clupeaformis larvae was promotional to a dry feed diet (Drouin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecific differentiation has been already assessed for several other traits of interest such as growth (e.g. Leithner and Wanzenböck 2015), feed conversion efficiency (e.g. Imsland et al 2000;Jonassen et al 2000), or disease resistance (e.g.…”
Section: Differences In Group Structure and Aggressive Interactions Bmentioning
confidence: 99%
“…Such feeds have been compared (Curnow, King, Bosmans, & Kolkovski, 2006;Curnow, King, Partridge, & Kolkovski, 2006) and are increasingly used for commercial aquaculture species (e.g., Katan et al, 2016;Watanabe et al, 2016) but also for experimental zebrafish (Farias & Certal, 2015). However, the suitability of such standard agglomerated commercial microdiets has rarely been tested, respectively, been published for European whitefish (Leithner & Wanzenböck, 2015). Most practitioners in aquaculture do not have the ability to manufacture their own microdiets, as this is very costly and time-consuming, and on the other hand, they do not have the professional skills and equipment to do such work.…”
mentioning
confidence: 99%